Thymus-derived rat lymphocyte receptor for cell surface antigens is a nonserologically defined product of the major histocompatibility gene complex. - Wekerle, H (1975)
Recognition of cell surface antigens by nonsensitized thymus-derived rat lymphocytes is not affected by antisera against immunoglobulin, yet can be effectively blocked by treatment of the lymphocytes with alloantisera raised against lymphoid cells. However, allo antisera induced by nonlymphoid cells do not inhibit recognition. Adsorption of blocking antisera on immunoglobulin-Sepharose columns does not decrease their blocking activity. Absorption of blocking alloantisera with liver and kidney homogenates removes the cytotoxic alloantibodies, yet does not affect the capacity of the antisera to block recognition. Anti-H1-1 alloantisera block antigen recognition only of lymphocytes of strains that share the H1-1 locus. These results suggest that the constant part of the thymus-derived lymphocyte receptor for cell-surface antigens is a product of the rat major histocompatibility locus, which is not identical with the serologically defined antigens.